1984
DOI: 10.1056/nejm198408093110603
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of HLA-A and HLA-B Matching on Graft and Patient Outcome after Cadaveric-Donor Renal Transplantation

Abstract: Data collected prospectively on 3811 renal transplantations performed between June 1977 and July 1982 by the 42 member institutions of the South-Eastern Organ Procurement Foundation were analyzed to determine the influence of donor-recipient HLA-A and HLA-B matching on patient and graft outcome. Well-matched recipients were more likely to have received kidneys from outside their own centers, were more highly presensitized, included fewer blacks, and were more likely to have lost an earlier graft. Multivariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…For kidney recipients, studies agree on a general trend toward improved graft survival with decreasing numbers of combined HLA-A, -B, and -DR MMs (2,4,6,27). The major impact of matching is due to the HLA-DR and -B loci, with the HLA-A locus much less significant (3,28).…”
Section: Discussionmentioning
confidence: 90%
“…For kidney recipients, studies agree on a general trend toward improved graft survival with decreasing numbers of combined HLA-A, -B, and -DR MMs (2,4,6,27). The major impact of matching is due to the HLA-DR and -B loci, with the HLA-A locus much less significant (3,28).…”
Section: Discussionmentioning
confidence: 90%
“…10 Studies performed in clinical solid organ transplants have sought to gain insight into immunologic parameters that could be important in altering the course of allograft tolerance, thus modifying the prognosis. Two main factors, donorrecipient HLA compatibility and the absence of preformed, donor-specific anti-HLA cytotoxic antibodies (giving rise to a positive crossmatch), are known to contribute to a more-favorable outcome in renal 11 and heart transplants. 12 In this study, based on studying the effect of a positive crossmatch on the outcome after liver transplant in our own patient population, it was found that both groups showed no statistical difference regarding total hospital and ICU stay, immunosuppressive use, rejection episodes, pulse steroid use, graft failure, mortality, and 5-year patient and graft survival.…”
Section: Discussionmentioning
confidence: 99%
“…Among HLAs, HLA-A, -B, -C, and DRB1 are important to transplantation [1][2][3][4][5][6][7][8] . Previous studies have shown that correct matching of this locus genotype improves the survival rate 7,9 and reduces immunological complications in graft-versus-host disease (GVHD) and graft rejection 1,10 .…”
Section: Introductionmentioning
confidence: 99%